Assessment of Disease State Awareness among Chronic Kidney Disease Patients Undergoing Hemodialysis in Divisional Headquarter Hospital Mirpur, Pakistan - Riaz, Sohail; Un Nisa, Zaib; Mushtaq, Saba; Ijaz, Qazi Amir; Sohail, Kashif; Khan, Abuzar (Journal of Pharmacy Practice and Community Medicine)
Background: Chronic Kidney Disease is a non-communicable disease which can often progress to kidney failure and can be a potential cause of some cardiovascular complications. There is need to assess awareness of disease to prevent progression. Objectives: The objective of the present study was to assess the disease state awareness among patients undergoing hemodialysis. Materials and Methods: A cross-sectional, non-experimental and questionnaire based study was conducted during December 2020 to Feburary 2021 in DHQ hospital Mirpur among patients undergoing hemodialysis. The questionnaire was translated into “Urdu” language, as it is native language of Pakistan. Descriptive and inferential statistics were used to analyse the results. SPSS version 20 was used for statistical analysis. Results: Amongst the 111 patients admitted in the hemodialysis center, 109 patients filled the questionnaire. Out of 109 patients, 58 (53.2%) were males. Urban residents were 56 (51.54%), 99 (90.8%) were Kashmiri, 30 (27.5%) had religious education, and 90 (82.6%) were non-occupational. Most of the patients were suffering from several co-morbidities such as, hypertension; 91 (83.5%), diabetes; 37 (33.9%), hyperlipidemia; 7 (6.4%), CVD; 19 (7.4%), hepatitis C; 23 (23.1%) and others; 15 (13.8%). Overall mean awareness score was 2.2±1.6. Among demographic variables, education and gender had significant p-values (p < 0.05). Conclusion: The awareness among patients was satisfactory but not adequate. Therefore, counseling programs about the disease and its management should be conducted in order to educate all the caretakers/patients with chronic kidney disease and end stage renal disease (ESRD).
Keywords: Renal insufficiency; Chronic; Renal dialysis; Awareness; CKD